2021
DOI: 10.6018/analesps.446871
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Spiritual Well-being and Tolerance of Uncertainty in Prediction of Happiness in Elderly

Abstract: Antecedentes: De acuerdo con las conceptualizaciones del bienestar espiritual, la intolerancia a la ambigüedad y la felicidad, este estudio se propuso investigar las influencias del bienestar espiritual y la tolerancia a la incertidumbre sobre la felicidad con respecto a los roles moderadores del sexo en los ancianos. Método: Participaron 120 ancianos de la ciudad de Shiraz, provincia de Fars, Irán. Para la recopilación de datos se utilizaron un cuestionario demográfico, el Inventario de Bienestar Espiritual (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 50 publications
(79 reference statements)
0
0
0
Order By: Relevance
“…This relationship between spiritual well-being and happiness is supported by the current literature (19,20). The finding of one study demonstrated that spiritual well-being could be a useful resource in improving the happiness of older people (21). In a similar study, spiritual well-being predicted 35% of the variance of happiness (22), further indicating the important role of spirituality in promoting happiness among elderly individuals.…”
Section: Discussionmentioning
confidence: 52%
“…This relationship between spiritual well-being and happiness is supported by the current literature (19,20). The finding of one study demonstrated that spiritual well-being could be a useful resource in improving the happiness of older people (21). In a similar study, spiritual well-being predicted 35% of the variance of happiness (22), further indicating the important role of spirituality in promoting happiness among elderly individuals.…”
Section: Discussionmentioning
confidence: 52%